Evaluación del potencial de producción de las Areniscas T del Campo A de Ecopetrol S.A. mediante simulación numérica (2019)
The following work determines the production potential of the T Sand located in the A field of Ecopetrol S.A. using numerical simulation. For doing this, it has been done a construction of a dynamic model and there has been a total of 14 different cases that evaluate the potential previously mentioned. The first case had been the Base Case and basing on the results of these cases, 13 cases have been proposed. In general, the A field has a quantity of 4 MMSTB of original oil in place. By simulating the cases mentioned before, and, using a time of 20 years for the prediction, it has been estimated that the 13th Case allows obtaining a recovery factor of 6.52% that is equal to 264.115 STB. The simulation of all these cases allows concluding that the T Sand can be produced using horizontal wells. However, the higher values of water saturation and the lower permeabilities of the reservoir will be a factor that is going to provoke the fast declination of these wells.